Women farmers and Andean seeds - Tapia, M.E.; Torre, A. de la (1998)
In rural areas, the conservation and use of plant genetic resources begins with women. As smallholder farmers, women are involved in all areas of the crop cycle from seed selection to planting, harvest, storage and processing. Within the household, women are responsible for food needs and welfare, including the gathering and utilization of food, fodder, fuel, medicinal plants and fibre. In these roles, women often determine which plant resources to conserve and use, which crop varieties to grow, which food products to keep for home consumption and which to sell at the local market. As illustrated by this case study of women farmers and seed in the Andes, rural women have a special interest in the diverse and multiple uses of plants and other biological resources, given their varied and complex responsibilities in rural households. The knowledge acquired as managers of these resources for livelihood, health and food security constitutes a knowledge system that both ensures subsistence and community needs, and contributes to the conservation and use of local varieties